English language learning motivation among UiTM students: a survey study / Nadzrah Sa’adan - Sa’adan, Nadzrah (2011)
This study investigates the English Language Learning Motivation among ESL learners of UiTM students. Specifically, it examines the types and frequency of English Language Learning Motivation used by high and low proficiency students, and between male and female students. Additionally, the study attempts to find out the relationship between the ESL learners’ overall language proficiency performance and their types of motivation used in second language learning. Apart from that, this study also attempt to find out the relationship between gender in types of motivation in ESL. The questionnaire used was the Attitude/Motivation Test Battery (AMTB) developed by Gardner (1985). The questionnaire consists of 2 sections. Section I is questions on the respondent’s demographic data which are gender and age and their proficiency level using their MUET results. Section II consists of variables which are: integrative motivation (items 1 to 12) and instrumental motivation (items 13 to 25) using 5 point Likert scale. The sample was comprised of 200 Bachelor of Administration Science students of UiTM Malacca City Campus, Malacca, Malaysia. Descriptive statistics, including Pearson and Independent T-Test were used to examine the relationship between types of motivation practiced in second language learning with respondents’ gender and proficiency. The results indicate that the students tend to have stronger instrumental motivation compared to integrative motivation. In terms in gender differences, the female respondents tend to have stronger instrumental and integrative motivation than male respondents. Meanwhile, in language proficiency differences, the high proficiency students tend to have high instrumental motivation rather than integrative motivation.